2001
DOI: 10.1002/sce.1012
|View full text |Cite
|
Sign up to set email alerts
|

Point and set reasoning in practical science measurement by entering university freshmen

Abstract: ABSTRACT:The procedural understanding of university students at the freshman level, prior to instruction, has been investigated in the context of experimental work in physics. A written instrument was used to explore students' ideas about data collection, data processing, and data comparison; in particular, the need to repeat measurements and the implications of the scatter associated with numerical and graphical data. Two types of reasoning used by students in the laboratory, viz. point and set reasoning, are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
48
0
25

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(76 citation statements)
references
References 16 publications
3
48
0
25
Order By: Relevance
“…Fred Lubben e membros do seu grupo de pesquisa (ALLIE et al, 1998;BUFFLER et al, 2001;LUBBEN et al, 2001), realizaram uma série de trabalhos que forneceu um importante suporte empírico para o desenvolvimento de um referencial no qual o pensamento e o raciocínio utilizados pelos estudantes durante o processo de medição e análise dos dados podem ser categorizados em dois tipos distintos, segundo os paradigmas Pontual e de Conjunto 2 . As diferenças entre os paradigmas podem ser vistas no Quadro 1.…”
Section: Paradigma Pontual E Paradigma De Conjuntounclassified
See 1 more Smart Citation
“…Fred Lubben e membros do seu grupo de pesquisa (ALLIE et al, 1998;BUFFLER et al, 2001;LUBBEN et al, 2001), realizaram uma série de trabalhos que forneceu um importante suporte empírico para o desenvolvimento de um referencial no qual o pensamento e o raciocínio utilizados pelos estudantes durante o processo de medição e análise dos dados podem ser categorizados em dois tipos distintos, segundo os paradigmas Pontual e de Conjunto 2 . As diferenças entre os paradigmas podem ser vistas no Quadro 1.…”
Section: Paradigma Pontual E Paradigma De Conjuntounclassified
“…Versões modificadas dessas questões podem ser encontradas em outras pesquisas (LEACH et al, 2000;LUBBEN et al, 2001).…”
Section: Questãounclassified
“…showed that more than 30% of the students mobilize the point reasoning when they collect and process data [11]. Many other studies have also highlighted pupils' and students' difficulties in analyzing data and understanding the measuring process.…”
Section: Pos(ffp14)236mentioning
confidence: 99%
“…Pupils tend not to realise that data collection is inherently random and often does not produce a single definitive 'right answer'; instead a spread of values are collected that approximate to that right answer (Lubben, Campbell, Buffler & Allie, 2001). This is why science curricula promote repeat measurements during experiments.…”
Section: Conclusion Résumémentioning
confidence: 99%